Exploring stress levels and physical activity patterns: A comparative analysis of blended and conventional learning methods - Yuliawan, Ely; Suhartini, Sugih; Yanto, Anggel Hardi; Kuntaro, Eko; Sofyan, (Journal Sport Area, 2023)
Changes in learning methods cause a crucial decrease in physical education needs and time of involvement in physical activity, which can affect individual stress levels. The objective of this study was to find out the comparison of physical activity patterns and stress levels between blended versus conventional learning methods. This study used quasi-experimental with a posttest-only approach with a control group design. The total subjects were 160 sports students from Universitas Jambi, who were divided into two groups (Experiment and Control) with average age of 21.69 ± 1.33 years, weight of 55.74 ± 6.48 kg, height of 170.10 ± 5.51 cm, and BMI of 21.06 ± 2.77 kg/m2. The results showed that the blended learning group had a lower level of physical activity when compared to their respective conventional groups. Furthermore, the stress level in the blended learning group had a moderate stress while the conventional group had a low-stress. Thus, the research findings have answered the question that physical activity can affect an individual’s stress level, and conventional learning methods are still the best method compared to blended learning methods. This finding can be used as a reference, especially for educators, both lecturers and teachers in schools, to be able to take a spiritual approach and invite students to do activities they like, such as exercise and recreation, to trigger a sense of enthusiasm in students to continue to improve their fitness degree. Therefore, this will have an impact on mental health, which can affect student stress levels much lower.